Implications of Annulment of Marriage on the Distribution of Joint Assets according to the Compilation of Islamic Law and National Law - Nurunnisa Nurunnisa; Rahmida Erliyani; Gilang Fitri Hermawan; Yehia Mohamed Mostafa Abdelhadi (Universitas Islam Negeri Antasari Banjarmasin, 2023)
Marriage, marriage dissolution due to marriage annulment and joint property which must be divided because of marriage annulment is one of the things that must strictly regulated by the state, but in Indonesia is still not regulated concretely, giving rise to a legal vacuum. So, this research aims to find out how the legal arrangements regarding the settlement of the division of joint assets after the cancellation of marriage and to find out how the implications of the cancellation of marriage on joint assets according to the Compilation of Islamic Law and National Law. The results are that first, the Compilation of Islamic Law and National Law cannot become the norm governing the distribution of joint assets if a marriage annulled. Second, there are no legal consequences for shared assets after the annulment of the marriage, but the ownership rights to the assets that have been mixed must be divided fairly between the parties. So that there must be codified arrangements so that there is no legal vacuum which can lead to multiple interpretations and in conducting marriages it would be better to make a marriage agreement to separate assets.